Jurisdiction by Cross-Reference - Lumen N. Mulligan (Washington University Law Review, 2011)
State and federal law often cross-reference each other to provide a rule of decision. The difficulties attendant to these cross-referenced schemes are brought to the fore most clearly when a federal court must determine whether such bodies of law create federal question jurisdiction. Indeed, the federal courts have issued scores of seemingly inconsistent opinions on these cross-referential cases. In this Article, I offer an ordering principle for these apparently varied, cross-referential jurisdictional cases. I argue that the federal courts only take federal question jurisdiction over crossreferenced claims when they, from a departmental perspective, maintain declaratory authority over the cross-referenced law. I defend this thesis by extensively exploring cross-referenced regimes in numerous modes. I also contend that this cross-referential ordering principle offers significant insights into the nature of federal question claims more generally. Namely, I assert that, contrary to the predominant view, the federal courts do not stand ready to hear cases in which the judiciary as a whole is deployed merely as a fact-finding forum under federal question jurisdiction. Further, I contend that this view of federal question jurisdiction comports with the original understanding of that font of jurisdiction, as well as principles of judicial independence, and that the Court’s tendency to vest federal question jurisdiction upon mere formal distinctions in these contexts often leads to separation-of-powers difficulties. As such, I advocate that jurisdiction over all cross-referenced regimes proceed on functionalist lines.
Keywords: Michigan v. Long 463 U.S. 1032 (1983); Federal jurisdiction; Judicial process; Separation of powers; Federal Tort Claims Act; United States